Analisis Sentimen Terhadap Citra Merek Starbucks Pada Media Sosial Twitter - Lusiana Nur Safitri; Nurhasan, Rohimat; Roji, Fikri Fahru (Jurnal E-Bis, 2024)
Brand image represents consumers' belief in a particular brand, forming their associations and perceptions. The shift from traditional to modern society due to globalization driven by technological advances has changed lifestyles. This transformation highlights the impact of Starbucks in introducing a new coffee culture to Indonesian consumers. The research methodology used is sentiment analysis using the VADER approach and Twitter as the main data source. The goal is to gain a deeper understanding of public sentiment towards the starbucks brand image on twitter social media. The observation results of this research show that many people use twitter as a medium to express various kinds of perceptions or sentiments, be it positive, neutral, and negative reviews. The findings of the sentiment analysis revealed that most of the people's responses were still neutral, with no positive or negative tendencies. By understanding the relationship between brand image and sentiment analysis, companies can take strategic steps to strengthen their brand image and positively influence consumer sentiment.